Survivors : Postholocaust Yiddish Poems in Non-Jewish Language - Waldinger, Albert (TTR)

(untitled) (Association canadienne de traductologie, 2001)
AbstractThis article, dealing with the translation of Postholocaust Yiddish poetry into non-Jewish languages like French, English and German, must necessarily sketch in a linguistic, literary and social background to prepare the ground for the complete understanding of the special task involved in the rendering of Jewish expression. (Conversion into Hebrew presents a far different challenge, described in a related study). Discussed here are literary movements like European Expressionism and Yiddish “Introspectivism” as practiced in the United States as well as the linguistic basis of these in Yiddish speech and poetic prosody and embodied in the translations of Cynthia Ozick (English), Charles Dobzynski (French) and Gabriele Kohlbauer-Fritz (German).